Conservation geopolitics. Issue 2 (8th November 2018) - Hodgetts, Timothy; Burnham, Dawn; Dickman, Amy; Macdonald, Ewan A.; Macdonald, David W.
Abstract: We reviewed recent work concerning the impact of geopolitics on wildlife conservation (and vice versa) and identified future priorities in conservation geopolitics research. Geopolitics is understood as both an analytical focus on geopolitical practices (especially concerning the behavior) of countries with respect to territory and national security and a set of theories developed to explain and predict those behaviors. We developed a typology of core geopolitical practices of relevance to conservation: territorial practices of colonization and the management of migrations and borders, and security practices relating to military, economic, and environmental security. We identified research that considers how these practices affect conservation situations and outcomes, noting the recent emergence of conceptual developments such as "environmental geopolitics" and "geopolitical ecology" that draw on multiple fields within the social sciences to theorize the links between geopolitics and environmental management. We defined a "geopolitical perspective" as a focus on geopolitical practices combined with an explicit engagement with geopolitical theory and identified conservation situations where this perspective could contribute to analytical clarity. We suggest the most pressing questions in conservation research to which the geopolitical perspective might contribute are how political and economic differences between countries affect biodiversity outcomes, how geopolitical practices to address those differences facilitate or frustrate conservation efforts, how national borders and human and wildlife movements can be better managed for the benefit of both, and how the most effective conservation strategies can be best selected to suit existing (and future) geopolitical realities. Abstract : Article impact statement : Political activities relating to national security and territory affect wildlife in diverse ways.